Energy-saving effect of automatic home energy report utilizing home energy management system data in Japan. (15th April 2017) - Iwafune, Yumiko; Mori, Yuko; Kawai, Toshiaki; Yagita, Yoshie
Abstract: This study assesses the effects of sending home energy reports utilizing the Home Energy Management System (HEMS) data to more than 1600 households in Japan. The treatment effect was verified using a panel data regression random effects model comparing the electricity consumption of a treatment group to which the report was sent with that of a control group that was not sent. The report was effective in winter and led to a 3.4% reduction in electricity consumption compared to the previous year in the average household. A further reduction of 5.4% for the households with higher electricity consumption for whom a significant reduction of 11.4% in the use of space heating was also observed. Although the treatment effect was not significant in summer for the average household, larger households reduced consumption by an overall average of 2%, with reductions of 6.8% and 7% in terms of space cooling and hot water use, respectively, from the previous month. In contrast, smaller households increased their space cooling consumption by more than 10% on average, which might be considered an undesirable boomerang effect. The accumulative treatment effect in a detached house group was also confirmed. Additionally, an accumulative two-year winter consumption reduction of 7.5% demonstrated the effectiveness of continual intervention. Highlights: Home energy reports utilizing the Home Energy Management System data was constructed. The effect was verified using a panel data regression random effects model in 1600 households. The report was effective in winter and led to a 3.4% reduction in electricity consumption. Households with higher electricity consumption reduced by 5.4% in winter, larger than average. The accumulative two-year winter consumption reduction of 7.5% was also confirmed.